Study of the Mechanical Properties of Ship Cleats Fabricated from Recycled High-Density Polyethylene - Nisazarifa, Adristi; Rosalina, Amanda; Nursyifaulkhair, Desrilia; Wibawa, I Putu Arta; Saputra, Muhammad Rizki Andika (Universitas Muhammadiyah Yogyakarta, 2025)
High-Density Polyethylene (HDPE), known for its high resistance to chemicals and impact, as well as its low carbon emission production process. However, the high production of HDPE plastic waste poses a significant challenge in the maritime world. This study focuses on efforts to recycle HDPE waste generated from the shipbuilding process at the Non-Metal Workshop of the Surabaya State Shipping Polytechnic (PPNS). This HDPE waste has great potential to be processed into ship components, including cleats. Cleats are essential devices on ships that function to tie ropes. HDPE waste is molded into new sheets using the Hot Press Compression Molding method, followed by tensile and bending tests. These values will be compared with the mechanical properties of virgin HDPE and simulated using ANSYS software to evaluate the cleat's resistance to tensile loads of 470 N, 600 N, and 730 N. Simulations show that the cleat can withstand loads of 470 N and 600 N, but fails plastically under a load of 730 N, with the stress exceeding its yield strength. The results of this study are expected to contribute to the development of more sustainable shipbuilding technology and encourage the development of other recycled products in the maritime industry.